2012
DOI: 10.1007/s10103-012-1086-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of erbium family laser on tensile bond strength of composite to dentin in comparison with conventional method

Abstract: The purpose of this study was to evaluate the effect of Er:YAG and Er,Cr:YSGG laser on tensile bond strength of composite resin to dentine in comparison with bur-prepared cavities. Fifteen extracted caries-free human third molars were selected. The teeth were cut at a level below the occlusal pit and fissure plan and randomly divided into three groups. Five cavities were prepared by diamond bur, five cavities prepared by Er:YAG laser, and the other group prepared by Er,Cr:YSGG laser. Then, all the cavities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 21 publications
0
24
1
2
Order By: Relevance
“…This may lead to thermal damage, chemical changes and resistance to demineralization. 24 Although erbium laser groups in our study did not show bond strength values as high as those in the common procedure, erbium laser treatment of bleached dentin surfaces seems to offer promising results. In the current study, the effect of change in irradiation parameters on the results was not evaluated.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This may lead to thermal damage, chemical changes and resistance to demineralization. 24 Although erbium laser groups in our study did not show bond strength values as high as those in the common procedure, erbium laser treatment of bleached dentin surfaces seems to offer promising results. In the current study, the effect of change in irradiation parameters on the results was not evaluated.…”
Section: Discussioncontrasting
confidence: 53%
“…The family of erbium family lasers (erbium: yttrium-aluminumgarnet [Er:YAG] and erbium, chromium: yttriumscandium-gallium-garnet [Er,Cr:YSGG]) with 2 different wavelengths has been widely used for cavity preparation and dental surface conditioning in adhesive esthetic procedures. [20][21][22][23][24] Erbium family lasers have wavelengths corresponding to the peak absorption of hydroxyapatite and water and hence. This results in a water-mediated ablative effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that due to higher collagen matrix content of intertubular dentin, laser energy absorption and ablation rate is higher in the intertubular area, in comparison with the peritubular area. 3 It has to be noted that the application of Er:YAG laser for cavity preparation seems to be safe for pulpal tissue, as it just rises the temperature up to 3°C, which is lower than 5.5°C change which is the threshold tolerated by a tooth. 12 Other studies confirmed that the application of Er:YAG laser seems to be safe and induce a similar pulpal response, when compared with conventional bur drilling.…”
Section: Discussionmentioning
confidence: 99%
“…These wavelengths are absorbed by water and hydroxyapatite, so they are suitable for removing dental hard tissues, and produce no cracks or melting area. 3 Advantages of using Er:YAG laser instead of dental drill include making no noise or vibration, and producing open dentinal tubules on dental surface without any smear layer. However, some studies showed that morphological changes of enamel surface lased with Er:YAG do not create effective bond between composite and dental surface.…”
Section: Introductionmentioning
confidence: 99%